Evaluation of treatment results in multifocal primary cutaneous anaplastic large cell lymphoma: report of the Dutch Cutaneous Lymphoma Group. (1st September 2018) - Melchers, R.C.; Willemze, R.; Bekkenk, M.W.; de Haas, E.R.M.; Horvath, B.; van Rossum, M.M.; Sanders, C.J.G.; Veraart, J.C.J.M.; Vermeer, M.H.; Quint, K.D.
Summary: Background: There is no consensus on the treatment of multifocal primary cutaneous anaplastic large cell lymphoma (C‐ALCL). Radiotherapy (RT) and methotrexate (MTX) are the current treatment options, but their efficacy is unknown. Recently, targeted therapies showed promising results in C‐ALCL, and may therefore be an attractive first choice of treatment. Objectives: To assess the efficacy of conventional treatment strategies for patients with multifocal C‐ALCL, and to define which patients may require novel targeted therapies. Methods: In this multicentre study, treatment was evaluated in patients initially presenting ( n = 24) or relapsing with multifocal C‐ALCL ( n = 17; 23 relapses). Distinction was made between patients with five or less lesions ( n = 36) and more than five lesions ( n = 11). Results: Treatments most commonly used were RT ( n = 21), systemic chemotherapy ( n = 9) and low‐dose MTX ( n = 7) with complete response rates of 100%, 78% and 43%, respectively, and an overall response rate of 100%, 100% and 57%, respectively. Four patients showed complete spontaneous regression. In total, 16 of 24 patients (67%) first presenting with multifocal C‐ALCL relapsed, including all five patients initially treated with CHOP (cyclophosphamide, hydroxydaunorubicin, oncovin and prednisone). Compared with patients presenting with two to five skin lesions, patients presenting with more than five lesions had a higher chance of developing extracutaneous relapse (56% vs. 20%) and more often died of lymphoma (44% vs. 7%). Conclusions: Patients with five or less lesions should be treated with low‐dose RT (2 × 4 Gy). Maintenance low‐dose MTX (20 mg weekly) is a suitable option in patients with more than five lesions. Targeted therapies may be considered in rare patients who are refractory to MTX or patients developing extracutaneous disease.